2020 25th International Conference on Pattern Recognition (ICPR) 2021
DOI: 10.1109/icpr48806.2021.9412166
|View full text |Cite
|
Sign up to set email alerts
|

3D Facial Matching by Spiral Convolutional Metric Learning and a Biometric Fusion-Net of Demographic Properties

Abstract: Face recognition is a widely accepted biometric verification tool, as the face contains a lot of information about the identity of a person. In this study, a 2-step neural-based pipeline is presented for matching 3D facial shape to multiple DNA-related properties (sex, age, BMI and genomic background). The first step consists of a triplet loss-based metric learner that compresses facial shape into a lower dimensional embedding while preserving information about the property of interest. Most studies in the fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Fig 1.C shows the structure of the auto-encoder network used to extract features based on 3D facial meshes as previously used in [52]. The first several layers of the encoder consist of spiral convolutional layers, which reduce the size of the input.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig 1.C shows the structure of the auto-encoder network used to extract features based on 3D facial meshes as previously used in [52]. The first several layers of the encoder consist of spiral convolutional layers, which reduce the size of the input.…”
Section: Methodsmentioning
confidence: 99%
“…However, as opposed to PCA, the disadvantage of an AE is that the latent variables are not necessarily uncorrelated. facial meshes as previously used in [52]. The first several layers of the encoder consist of spiral convolutional layers, which reduce the size of the input.…”
Section: Auto-encodermentioning
confidence: 99%
“…Established mesh decimation techniques used in many geometric deep learning methods reduce the number of vertices such that a good approximation of the original shape remains, but they result in irregularly sampled meshes at different steps of resolution. In contrast, we used a 3D mesh down and up-sampling scheme that retains the property of equidistant mesh sampling as defined in [24]. Starting from five initial points, the refinement is done with loop subdivision by splitting each triangular face of the mesh into four smaller triangles by connecting the midpoints of the edges.…”
Section: Pipeline Designmentioning
confidence: 99%
“…In-house experiments showed that other sampling schemes are equally effective and can be used instead. The number of spirals in each layer was chosen empirically based on the previous and related works [24], as well as in other in-house projects where similar facial data structures are used. The length of the spiral filters was set to 19 for the first two layers with the highest resolution, and a length of 6 was chosen for the following layers with lower resolution.…”
Section: Pipeline Designmentioning
confidence: 99%